Modulation of the pre-metastatic bone niche: molecular changes mediated by bone-homing prostate cancer extracellular vesicles - Brown, Thomas J.; Rutland, Catrin S.; Choi, Katie K.; Tse, Feng; Peffers, Mandy J.; Mongan, Nigel P.; Arkill, Kenton P.; Ritchie, Alison; Clarke, Philip A.; Ratan, Hari; Allegrucci, Cinzia; Grabowska, Anna M.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Prostate cancer (PCa) is a leading male malignancy worldwide, often progressing to bone metastasis, with limited curative options. Extracellular vesicles (EVs) have emerged as key players in cancer communication and metastasis, promoting the formation of supportive microenvironments in distant sites. Our previous studies have highlighted the role of PCa EVs in modulating osteoblasts and facilitating tumor progression. However, the early pre-metastatic changes induced by PCa EVs within the bone microenvironment remain poorly understood. To investigate the early effects of repeated exposure to PCa EVs in vivo, mimicking EVs being shed from the primary tumor, PCa EVs isolated from cell line PC3MLuc2a were fluorescently labelled and repeatedly administered via tail vein injection to adult CD1 NuNu male mice for a period of four weeks. In vivo imagining, histological analysis and gene expression profiling were performed to assess the impact of PCa EVs on the bone microenvironment. We demonstrate for the first time that PCa EVs home to both bone and lymph nodes following repeated exposures. Furthermore, the accumulation of EVs within the bone leads to distinct molecular changes indicative of disrupted bone homeostasis (e.g., changes to signaling pathways such as Paxillin p=0.0163, Estrogen Receptor p=0.0271, RHOA p=0.0287, Ribonucleotide reductase p=0.0307 and ERK/MAPK p=0.0299). Changes in key regulators of these pathways were confirmed in vitro on human osteoblasts. In addition, our data compares the known gene signature of osteocytes and demonstrates a high proportion of overlap (52.2%), suggesting a potential role for this cell type in response to PCa EV exposure. No changes in bone histology or immunohistochemistry were detected, indicating that PCa EV mediated changes were induced at the molecular level. This study provides novel insights into the alterations induced by PCa EVs on the bone microenvironment. The observed molecular changes indicate changes in key pathways and suggest a role for osteocytes in these EV mediated early changes to bone. Further research to understand these early events may aid in the development of targeted interventions to disrupt the metastatic cascade in PCa.